Socio-demographic and behavioural characteristics of illegal motorcycle street racers in Malaysia - Wong , L.P. (BioMed Central, 2011)
BACKGROUND: This study sought to understand the factors associated with street racing among the illegal motorcycle racers in Malaysia or known as the "Mat Rempit".